Optimalisasi Fintech Pada Pengembangan Pariwisata Berkelanjutan Pada Pantai Baro Gebang - Hikmah, Anur; Vidiati, Cory (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Baro Gebang Beach has great potential to develop as a sustainable tourism destination. The main challenge in resource management is combining economic growth with environmental conservation. Fintech is present as an innovative solution to support tourism development in this area, by providing access to capital, community-based funding, and increasing operational efficiency. Through P2P lending, local craftsmen in Baro Gebang Beach can expand their businesses, create new jobs, and increase income. This literature review emphasizes the importance of digital literacy and cross-sector collaboration in creating an inclusive and sustainable tourism ecosystem.